Friends with benefits? - Does gut microbiota of Spodoptera littoralis affect insecticide resistance and are there any costs of insecticide resistance development? - Heithausen, Sarah (2021)
The insect gut microbiota has many important functions for insects such as detoxification of host plant toxins. Recently there has been a growing interest on the effect of insect gut microbiota on insecticide resistance development. Insecticide resistance is a growing concern for food security and sustainable agriculture. More knowledge about the relationship between gut microbiota and insecticide resistance development might help to gain more insight into the ecology behind resistance development and to refine pest management strategies. In this thesis I aimed to understand if gut microbiota can affect insecticide resistance, if there are any costs of resistance development and if gut microbiota can mediate such costs as well as any potential consequences of pesticide exposure on insect life history traits. To answer these research questions, I tested how the gut microbiota of a Cypermethrin-resistant and a susceptible Spodoptera littoralis lab strain affected survival of exposition with the insecticide Cypermethrin. The larvae had either been treated with antibiotics (Streptomycin + Ampicillin) prior to the exposition experiments or not, and thus had either a reduced or intact gut microbiota. The larvae that had been treated with antibiotics prior to the insecticide exposition continued to receive antibiotics after exposition as well. Following the exposition experiment I observed life history traits of the insects for the rest of the insect generation and recorded larval growth rate, larval development time, pupation rate, pupal weight, pupal development time, eclosion rate, survival until adulthood and female adult life span. Furthermore, I performed an oviposition experiment to measure female fecundity. The results showed that survival of insecticide exposition was higher for the resistant strain and for larvae with damaged gut microbiota from both the resistant and the susceptible strain. Insecticide resistance did not seem to depend on detoxification through resistant gut bacteria. Insecticide exposition had a negative effect on larval survival but increased larval growth rate, pupal weight, and fecundity. Thus, consequences of insecticide exposure might be long lasting and reach beyond and arise later than the initial survival following exposition. The resistant strain had shorter larval and pupal development time and increased pupation rate, but lower larval growth rate, pupal weight, fecundity, and survival until adulthood compared to the susceptible strain. Thus, resistance development seemed to create fitness costs for resistant insects. Gut microbiota seemed to have a mediating effect on the costs of resistance as well as on the consequences of insecticide exposition. My results thus indicate that gut microbiota is not contributing to Cypermethrin resistance of S. littoralis larvae. Instead, insecticide resistance may increase if pathogenic gut bacteria are removed. My results indicate further that both insecticide exposure, insecticide resistance and gut microbiota presence could have positive or negative effects on S. littoralis larvae depending on life stage and whether traits are involved in growth or survival. Implications of these results for pest control and further research are discussed.